Climate Change Education For Children Using E-Klim - Malik, Amarullah; Muhlis Suja'i, Cecep Abdul (EduBase : Journal of Basic Education, 2025)
The worsening waste crisis poses a serious challenge to environmental sustainability. Objective: This study introduces E-Klim, an innovative climate education model that combines waste management with child-based environmental learning through participatory visual methods. Novelty: This model offers a unique approach by integrating visual education for children, waste-based philanthropic actions, and community empowerment in one integrated framework. Methods: Using Participatory Action Research (PAR), this study actively involved children, communities, religious institutions, NGOs, and local governments in developing interactive tools such as the 'Match Cause and Effect' game and the 'Green Challenge' activity. Results: The research findings show: (1) a significant increase in children's understanding of climate change through a visual approach, (2) the transformation of the recycling system into a community philanthropic movement, and (3) the implementation of real actions such as tree planting. Conclusion: E-Klim has proven to be an effective framework that not only solves the waste problem but also creates a circular economy based on local values, while strengthening environmental education for the younger generation through innovative participatory methods.